Users' Perspectives with Agricultural Research and Development (UPWARD) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
UPWARD is an Asian network of scientists and development specialists linking users and R&D professionals together for more effective agricultural innovation. It seeks to link users and R&D professionals for more effective agricultural innovation; bring sustained benefits to less favored farming areas and marginalized groups, especially women; and work with households and local communities as key actors in research and learning activities. As a Partnership Program of CIP, it serves as platform for adapting and scaling up technological innovations developed by CIP research.